Effect of cimetidine treatment in the prevention of gastric ulcer relapse: a one year double blind multicentre study. Issue 9 (September 1983) - Hentschel, E; Schütze, K; Weiss, W; Rüdiger, E; Judmair, G; Reichel, W; Kerstan, E; Horton, J
Abstract : One hundred and forty six gastric ulcer patients were given open treatment using 1 g cimetidine daily to heal their ulcers. Of 130 who completed the acute treatment period of eight weeks, 112 (86%) had healed ulcers. Of these 112 patients with healed ulcers, 108 entered a one year double blind study to compare the effect of cimetidine maintenance therapy (400 mg at night) with placebo. Of the 84 patients available for assessment at the end of one year, 86% in the cimetidine treated group were in remission compared with 45% in the placebo treated group (chi 2 = 15.03; p less than 0.001). There were similar losses from non-compliance and drop out in both groups. The incidence of untoward effects and significant drug related laboratory abnormalities was low. The results indicate that cimetidine heals nearly 90% of acute gastric ulcers within eight weeks and that subsequent low dose maintenance treatment at night offers a considerable benefit over placebo therapy.